RELATIONSHIP BETWEEN SERUM HOMOCYSTEINE LEVEL WITH THE SEVERITY OF ACUTE MYOCARDIAL INFARCTION ASSOSIATED WITH GENSINI SCORE - Muhammad Arief Pratama, Ratna Akbari Ganie & Zulfikri Mochtar (International Journal of Research Science and Management, 2020)
Background Coronary Arterial Disease (CAD) is currently one of the main and first causes of death in developed and developing countries, including Indonesia. Acute myocardial infarction (AMI) is a common cardiac emergency caused by unstable ischemic syndrome. In practice, abnormalities are diagnosed and assessed based on clinical evaluation, electrocardiogram, biochemical testing, invasive and non-invasive imaging, and pathological evaluation. Homocysteine is an amino acid that has a sulfur group involved in the methionine cycle, namely in the remetilation pathway and the transulfuration pathway. The function of this cycle is to donate the methyl groups needed by various body molecules and the synthesis of glutathione. Method This is a analytic observational research with cross-sectional approaches. A total of 50 subjects with acute myocardial infarction, serum homocysteine levels were examined as well as coronary angiography examination. The severity of acute myocardial infarction was assessed by a gensini score which was then statistically analyzed. Data were analysed using computer statistic software. Results Median gensini score was 52 (6-94). From laboratory tests, the average serum homocysteine level was 10.28 ± 4.61 µmol / L. Using the Spearman correlation, the correlation between serum homocysteine levels and gensini scores was p = 0.001 with r = 0.445. Conclusion From the results of the study concluded that there was a significant relationship between serum homocysteine levels with the severity of acute myocardial infarction associated with Gensini scores.